Whipple's disease: comparison of histology with diagnosis based on polymerase chain reaction in four consecutive cases. Issue 3 (March 1997) - Müller, C; Petermann, D; Stain, C; Riemer, H; Vogelsang, H; Schnider, P; Zeiler, K; Wrba, F
Abstract : BACKGROUND: Polymerase chain reaction (PCR) based detection of species specific sequences of the 16S rRNA gene of Tropheryma whippelii is a recently described method for diagnosis of Whipple's disease. AIMS: Comparison of histology with PCR in mucosal samples of patients with Whipple's disease before, during, and after treatment. Detection of T whippelii in peripheral blood mononuclear cells as a non-invasive test for infection. METHODS: Four consecutive patients with histologically proven Whipple's disease were studied prospectively. RESULTS: In untreated patients biopsy specimens taken from regions with PAS positive macrophages gave a positive result with PCR for T whippelii; however, a PCR signal was also found in tissue biopsy specimens from mucosal regions with negative histology. In two of the patients the PCR performed with nucleic acids extracted from peripheral blood mononuclear cells was positive. After treatment with sulfamethoxazole/trimethoprim the PCR became negative after one month in two patients and after two months in the third patient treated, whereas PAS positive macrophages were found throughout the treatment period in two patients and disappeared in only one of them thereafter. CONCLUSIONS: Detection of T whippelii specific sequences based on the PCR is useful to confirm the diagnosis, is able to detect a positive signal in samples taken from histologically negative mucosal areas, and can be used to monitor treatment. The PCR can sometimes be positive in peripheral blood mononuclear cells, but this cellular compartment cannot be taken as a substitute for duodenal biopsy specimens in the diagnosis of Whipple's disease.